NILAI PENDIDIKAN ISLAM DALAM RUQYAH SYAR’IYYAH PADA KOMUNITAS RUQYAH SYAR’IYYAH ALHAQ BENGKULU - M Luthfi (Pascasarjana UIN Fatmawati Sukarno Bengkulu, 2017)
Abstract: Ruqyah became a phenomenon. A term that is still felt strange in the ears of the Muslims. This interesting phenomenon coincided with the increasingly widespread practices of polytheism, especially in the case of treatment performed by shamans and paranormal. On the other hand understanding of the Muslims will ruqyah very least, can be said to hear his name alone can be said recently. From where the need for the public to understand the importance Ruqyah Syar’iyyah as exemplified by the Prophet in order not to get stuck with a variety of treatments that appear un-Islamic but essentially idolatry. Community presence Ruqyah Syar’iyyah Alhaq Bengkulu (RSAB) seeks to provide solutions to the problems. From some keyataan above, formulated the problems include: educational values of Islam in Ruqyah Syar’iyyah in Community RSAB and how peruqyah spiritual experiences during the run ruqyah therapy in Community RuqyahSyar’iyyahAlhaq Bengkulu. The research objective was to determine the values of Islamic education in Ruqyah Syar’iyah. While the benefits of the research itself as an input to fortify the people not to get caught various shamanic practices and treatment of polytheism. Results of research and analysis of the data and conclusions found that the values of Islamic education in the Community syar’iyyah ruqyah Ruqyah Syar’iyyahAlhaq Bengkulu include Value Faith, Values Tauhid, Moral Values, Tolerance Values, Values Honesty, Value Ikhlas, resignation Values, Values constancy and Values Faredah. With ruqyah can help a lot of people that is working to find a cure and completeness of the problem through the Quran and prayers. Treatment with ruqyah is necessary for Muslims to avoid the various treatment idolatry.